Development of Angry Birds Game on Manipulative Movement Skills of Elementary School Children - Sinulingga, Albadi; Simatupang, Nurhayati; Rahman, Atikah (Indonesian Journal of Sport Management, 2025)
he type of research method used in this angry bird game development research is the research and development method (Research and Development), which aims to develop and validate learning products. This study’s research and development (R & D) development model from Brog and Gall consists of ten steps. The subjects in the small group in this study were 20 students of class IV A MIS Nurul Amal Labuhan Batu Selatan. The subjects in the large group in this study were 40 students of class IV B and IV C MIS Nurul Amal Labuhan Batu Selatan. The small group trial obtained an empirical score of 78.62% (Quite Valid or Effective), so the Angry Birds game product is effective for manipulative movement. The expert revision in the small group trial was 80% (Valid). Although it was valid, the expert still provided revisions on the angry bird game for improvement. In the large group trial, based on the values ​​obtained, it was known that the empirical score obtained was 89.25% (Valid or Very Effective). The expert revision in the large group trial was 92.50% (Valid). This means that this study is sufficient to determine the validity of the angry bird game on the manipulative movement skills of grade IV students of MIS Nurul Amal Labuhan Batu Selatan. The effectiveness and efficiency test results above are 95% in the valid or very effective category. So, that means the development of this angry bird game can be applied later in learning elementary school children’s basic manipulative movement skills.